The perverse pleasure of the uncanny in Silvina Ocampo - Murillo-Chinchilla, Veronica (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This article analyzes six short stories by the Argentinian author: Nosotros, La propiedad, Los amigos, La oración, Mimoso and La boda. The study made use of two theoretical frameworks: first, the theory elaborated by Sigmund Freud on his 1919 essay Das Unheimliche; second, Michel Foucault's study about the origin of the social notion of anomaly.The psychoanalytical theory propoundedby Freud has become a mandatory model in which the uncanny implies the horror of the embodimentof something that should have remained hidden. However, this article suggest the possibilityfor the characters to experience pleasure in response to the grisly events recounted.The stylistic ambiguity and the semantic presuppositionsplay a crucial role in the interpretation of the text, as well as the establishment of a fascinating ans startling narrative atmosphere. In addition, Foucault's postulates suggest interpretations of how the conception of the term anomaly, from a psychiatric standpoint, and the resulting moral connotations in the way how the individual perceives and juges others establish a rigid social structure, leaving almost no room for dissension.
Keywords: fantasy literature; the uncanny; pleasure; anomaly; normalcy; blame; Silvina Ocampo; women's literature; Latin American literature